The Acute Effects of a Single Session of Expiratory Muscle Strength Training on Blood Pressure, Heart Rate, and Oxygen Saturation in Healthy Adults - Laciuga, Helena; Davenport, Paul W.; Sapienza, Christine (Frontiers in Physiology, 2012)
Expiratory muscle strength training (EMST) is a rehabilitative program that has been tested for outcomes related to respiratory muscle strength, cough, swallow, and voice function in healthy young adult, elderly individuals, and in patients with progressive neurodegenerative disease. Because EMST has been used in patient care, the associated cardiovascular responses during EMST are of importance. This study investigated the changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and oxygen saturation (SpO2) during one session of EMST in healthy, young adults as a preliminary study of device safety. Thirty-one participants completed a single session of 25 trials with the EMST device. Valsalva maneuvers were performed at the beginning and at the end of the EMST trials for task comparison. The SBP, DBP, HR, and SpO2 were recorded at the baseline and after completing the following tasks: a Valsalva maneuver, 12 trials using the EMST device, 13 trials using the EMST device, and 5 min of rest following the EMST session. A mixed linear model tested for changes across the six time points. The results indicated no significant change of SBP, DBP, HR, or SpO2 during or following the EMST trials or after performing the Valsalva maneuver. The results suggest that EMST does not elicit significant fluctuations of blood pressure, HR, and SpO2 in healthy young adults even when considering the effects of covariates on the outcomes measures.